Product development and quality assessment of chicken patty incorporated with bamboo (Dendrocalamus latiflorus) shoot - Paler, Juliane Czarina Bendijo (2010.)
The study focused on the product development and quality assessment of chicken patty incorporated with bamboo shoots.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Bamboo shoot--Dendrocalamus latiflorus; Chicken patty